2012
DOI: 10.1088/2041-8205/756/1/l16
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Rise and Fall of the First Stars by Their Impact on Cosmic Reionization

Abstract: The intergalactic medium was reionized before redshift z ∼ 6, most likely by starlight which escaped from early galaxies. The very first stars formed when hydrogen molecules (H 2 ) cooled gas inside the smallest galaxies, minihalos of mass between 10 5 and 10 8 M ⊙ . Although the very first stars began forming inside these minihalos before redshift z ∼ 40, their contribution has, to date, been ignored in large-scale simulations of this cosmic reionization. Here we report results from the first reionization sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
194
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(197 citation statements)
references
References 46 publications
3
194
0
Order By: Relevance
“…Our simulations lack the resolution and the physics to follow the formation of stars in minihaloes, i.e., haloes with virial temperatures below 10 4 K. Ionization by these stars is expected to increase the optical depth by 0.03 (e.g., Shull & Venkatesan 2008;Ahn et al 2012;Wise et al 2014). If these stars evolve into accreting black holes, the optical depth may be further increased due to the pre-ionization of the IGM by X-rays (e.g., Ricotti & Ostriker 2004).…”
Section: Overview Of Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our simulations lack the resolution and the physics to follow the formation of stars in minihaloes, i.e., haloes with virial temperatures below 10 4 K. Ionization by these stars is expected to increase the optical depth by 0.03 (e.g., Shull & Venkatesan 2008;Ahn et al 2012;Wise et al 2014). If these stars evolve into accreting black holes, the optical depth may be further increased due to the pre-ionization of the IGM by X-rays (e.g., Ricotti & Ostriker 2004).…”
Section: Overview Of Simulationsmentioning
confidence: 99%
“…The optical depth towards reionization, τreion = zstart z=0 necdt, where ne is the number density of free electrons and zstart 30 is the redshift at which reionization begins, is an important integral constraint on the reionization history (e.g., Alvarez et al 2006;Shull & Venkatesan 2008;Ahn et al 2012). For the computation of the optical depth, we assume a hydrogen mass fraction X = 0.75, and that the fraction of ionized hydrogen is equal to that in our simulations, which assume X = 1.…”
Section: Overview Of Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed most reionization simulations in large boxes used to implement atomic-cooling halos only, while this may underestimate the photon budget in the early stage of reionization. In a large-scale (box size of 114/h Mpc comoving) simulation of cosmic reionization (with ray-tracing method), Ahn et al (2012) used the conditional halo bias found in Section 4.2.1 of this paper to include minihaloes, which could not otherwise have been realized due to numerical resolution. This way, they could span the full dynamic range of haloes -both minihaloes and atomic-cooling haloes -responsible for emitting hydrogen-ionizing and H2-dissociation radiation, and observed that the reionization process is extended further in time to comply better with several observational constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an additional simulation was performed, including this new physics, in an even larger volume (∼ 600 Mpc; I. T. Iliev et al, in preparation). Ahn et al (2012) expanded the mass range even further by accounting for starlight emitted by minihalos (10 5 -10 8 M ) as well. In addition to their Jeans-mass filtering in ionized regions, they may also be suppressed if molecular hydrogen in minihalos is photodissociated by Lyman-Werner (LW) band photons in the UV background below 13.6 eV also emitted by the sources of reionization.…”
Section: Introductionmentioning
confidence: 99%